Validation of an equation predicting highly unsaturated fatty acid (HUFA) compositions of human blood fractions from dietary intakes of both HUFAs and their precursors - Strandjord, Sarah E.; Lands, Bill; Hibbeln, Joseph R. (Prostaglandins, leukotrienes and essential fatty acids, 2018)
Proportions of omega-3 (n-3) and omega-6 (n-6) in 20- and 22-carbon highly unsaturated fatty acids with 3 or more double bonds (HUFA) accumulated in tissue HUFA (e.g., the %n-6 in HUFA) are biomarkers reflecting intakes of n-6 and n-3 fatty acids. An empirical equation, referred to here as the Lands’ Equation, was developed previously to use dietary intakes of n-6 and n-3 HUFA and their 18-carbon precursors to estimate the %n-6 in HUFA of humans. From the PubMed database, we identified clinical trials reporting (a) dietary intake of at least linoleic acid (18:2n-6) and alpha-linolenic acid (18:3n-3), and (b) the amounts of at least arachidonic acid (20:4n-6), eicosapentaenoic acid (20:5n-3), and docosahexaenoic acid (22:6n-3) in lipids of plasma, serum, or red blood cell. Linear regression analyses comparing reported and predicted %n-6 in HUFA gave a correlation coefficient of 0.73 (p<0.000000) for 34 studies with 92 subject groups. These results indicate that circulating HUFA compositions can be reliably estimated from dietary intake data that not only includes n-3 and n-6 HUFA consumption, but also includes consumption of 18 carbon n-3 and n-6 precursor fatty acids. •Omega-3/omega-6 highly unsaturated fatty acids (HUFA) are disease risk biomarkers.•Precursor dietary fats are not typically included in estimating n-3 and n-6 HUFAs.•Reliable HUFA biomarkers estimates require both dietary precursor fats and HUFAs.